Effects of learning physics using Augmented Reality on students' self‐efficacy and conceptions of learning. (20th August 2020) - Cai, Su; Liu, Changhao; Wang, Tao; Liu, Enrui; Liang, Jyh‐Chong
Abstract: The Augmented Reality (AR)‐based learning environment not only provides educators with novel ways to present learning materials but also give learners the opportunity to spontaneously interact with the material. Previous studies have shown that AR has many advantages in education; however, few focuses on the mechanisms behind promoting inquiry motivation, such as the effect of AR on learners' self‐efficacy and conceptions of learning. This study developed an AR‐based wave‐particle duality learning application, "AROSE, " to explore the effect of AR technology on students' self‐efficacy and conceptions of learning physics. A quasi‐experimental study method was used, and 98 high school students aged between 16 and 18 were randomly assigned to experimental and control group. After a 4‐week intervention, it was found that integrating AR technology into physics classrooms can (1) significantly enhance students' physics learning self‐efficacy, as indicated by understanding of concepts, higher‐level cognitive skills, practice and communication; (2) guide students to be more inclined to higher‐level conceptions of learning physics rather than lower ones; and (3) stimulates students' motivation to learn more deeply.